FEASFeasibility analysis of business abon catfish small medium (SMEs) in the district Kampar - Yusuf, Yusbar; Mayes, Anthoni; ', Lusiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine whether or not the business shredded catfish on Small and Medium Enterprises to run. The location of this study conducted in Kampar district.The type of data used are secondary data sourced from Statistics KamparKampar district PDRB Contribution of economic sectors to PDRB Kampar, Kampar and Contributions Population According Livelihood Year 2009-2012. Primary data is sourced from Shredded Entrepreneur Catfish in Kampar district. The analytical method used is a feasibility analysis to determine the feasibility conditions shredded catfish in Kampar district views from the large value of Net Present Value (NPV),Benefit Cost Ratio (B / C ratio) and Internal Rate of Return (IRR).Based on the results of the feasibility analysis calculation shows that the effort shredded catfish feasible. It can be seen from the feasibility test using the calculation of NPV, B / C ratio and IRR. NPV value obtained for 369 111 369 111 This suggests that> 1 means business shredded catfish in Kampar regency feasible. The B / C ratio of 1.094 is obtained showed that 1.094> 1 means business shredded catfish feasible. Values obtained for 68.54% IRR shows that 68.54%> 14% means business shredded catfish feasible.Keywords: Feasibility Study, Small and Medium Enterprises